FAKTOR-FAKTOR YANG MEMENGARUHI FINANCIAL SUSTAINABILITY STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Tita Nurvita; Efri Dayanti (Lembaga Riset dan Pengabdian Masyarakat (LRPM) Institut Bisnis Nusantara, 2021)
The research tries to analyze determinant factors of financial sustainability in manufacture companies listed in Indonesia Stock Exchange from 2015 to 2019. The dependent variable used is financial sustainability which proxies with sustainability growth rate and profitability. The independent variables are working capital turnover (WCTO), receivable turnover (RTO), inventory turnover (ITO), and payable turnover (PTO). We collect data from www.idx.co.id and www.idnfinancial.com and got 260 firm years sample data. The data were running by SPSS 18. The result shows that only RTO and PTO that has impact to financial sustainability in company. Meanwhile the other aspects don’t have any significant impact.